Study on Groundwater Quality in Concern to Potent Pollution at Secondary Block P17-5N Delta Telang II (Case Study of Muliasari Village, Tanjung Lago Banyuasin District, South Sumatera Province Indonesia) - Lilian Novarika; Robiyanto Hendro Susanto; Muhammad Faizal; Poedji Loekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
Research had been carried out on tidal marshes condition at tertiary channel Muliasari Village and the effect of land user behavior on water and soils quality. The aimed of research is to evaluate water and soil quality and potent pollution due to fertilizer and pesticide utilization. The research methods are survey and qualitative approach using observation and directed interview with questionnaire aid. Water and soils samples were taken by purposive sampling method. Measurement obtained soils has pH 4.59 and 3.92 for TC4 and TC5 respectively. Cation exchange capacity is 21.65 mg/100 g or TC4 and 20.62 mg/100 g for TC5. C-organic contained in both TC4 and TC5 are very high whereas Total-N is moderate hence ratio C/N has moderate value. P2O5 detected as 81.55 ppm at TC4 and 36.06 ppm at TC5. According to Soils Research Centre Bogor, TC4 and TC5 has moderate value of N (35%) while P and K very high (81.55 ppm and 103.32 ppm). Scoring result concluded that soils is in good health and has 76% (TC4) and 73% (TC5). Storet method confirmed score result for soils as B-class or in good condition. According to these result, TC4 and TC5 of Muliasari Village was lightly polluted and still has good prospect as crops land. Key Words: Tidal zone, Water quality, pollution